Forensik Mobile pada Layanan Media Sosial LinkedIn - Imam Riadi; Anton Yudhana; Mushab Al Barra (JISKA (Jurnal Informatika Sunan Kalijaga), 2021)
The research explores mobile forensic on LinkedIn social media. Forensic mobile finds digital evidence of job hoax cases in LinkedIn, investigation using the NIST (National Institute of Standard and Technology) method. Data collection techniques using Andriller tools in investigations. Data examination using tools Root Browser, Autopsy in the forensic process. data analysis using tools MOBILedit in the forensic process. The investigation found digital evidence of log activity, a status update on LinkedIn. Other results found in the investigation are 17 WiFi password, 117 download history, 263 phone calls, 1 file deleted, 1 file hidden, and 1 file raised, the research has reached the expected target.